Study of an endophytic fungus from Aquilaria malaccensis Lamk - Mohammad Shoeb; Shahanara Begum; Nilufar Nahar (Bangladesh Pharmacological Society, 2010)
Nine endophytic fungal strains labeled as AL-1, AL-2, AS-1, AS-2, AS-3, AS-4, AR-1, AR-2 and AR-4 were isolated from the medicinal plant Aquilaria malaccensis Lamk. Three compounds 1,7-dihydroxy-3-methoxyanthraquinone, propyl p-methoxy phenyl ether and 6-methoxy-7-O-(p-methoxyphenyl)-coumarin were isolated from the ethyl acetate extract of the strain AL-2 by silica gel column chromatography and HPLC. The structures of isolated compounds were elucidated by spectroscopic techniques i.e. UV, IR, 1D and 2D NMR. Extracts of the strain AL-2 were assessed for antibacterial activities against Gram positive and Gram negative bacteria and general toxicity against brine shrimp lethality assay. The ethyl acetate extract showed only mild activity against two Gram positive bacteria (Bacillus cereus and Staphylococcus aureus).